Dietary patterns and their association with obesity and cardiometabolic risk factors among adolescents in the southern region of Peninsular Malaysia - Emi, Nor Aishah (2019)
While the importance of high intake of energy dense foods for the development of cardiovascular disease (CVD) has been emphasised recently in the Western countries, this was not fully elucidated among Malaysian adolescents. Diet is a modifiable risk factor for CVD in adulthood and is therefore, likely to also be an important early CVD risk factor in adolescence. This cross-sectional study aimed to examine the associations between adolescents’ dietary pattern (DP) and cardiometabolic risk factors (CRF) and obesity. DP offers a new approach in nutritional epidemiology as compared to single nutrient or food groups which is more practical to be translated into recommended advice for use among adolescents. Reduced Rank Regression (RRR) used to derive DP in this study is a hybrid method which combines both exploratory and hypothesis-oriented approach simultaneously. CRF is referred to any risk factor which may increased the odds of developing CVD and diabetes mellitus. CRF assessed in this study are abnormal biochemical levels including fasting blood glucose, serum insulin and lipid profile as well as the presence of dyslipideamia. Obesity which is one of the major CRF is catagorised separately from CRF in this study in order to examine its independent association with identified DP. A total of 933 adolescents aged 13 years old from three southern states in peninsular Malaysia, namely Negeri Sembilan, Melaka and Johor agreed to participate in this study. Anthropometric measurements including weight (kg), height (m) and WC (cm) of adolescents were measured, and BMI z-score was calculated according to the 2006 World Health Organisation (WHO) BMI-for-age growth standards. Biochemical data of 507 adolescents were measured. Self-reported physical activity and socio demographic information were collected from the study adolescents and their parents. Five hundrends and eighty three adolescents provided valid dietary information assessed using a validated food frequency questionnaire (FFQ). The RRR was used to identify a DP that explained the most variation in four chosen response variables, namely dietary energy density, fibre density, percentage of energy from total fat and percentage of energy from sugar. The response variables chosen in this study are hypothesized to be associated with CRF and obesity based on prior scientific evidence from previous studies in Western countries. The identified ‘high sugar, high fibre, high energy density and low fat’ DP, which explained 35% of the variation in all response variables was characterised by high intakes of sugar-sweetened beverages, fruits, sweets and low intakes of meat and meat-based dishes, and cereal and cereal-based dishes. The associations were examined using regression models between DP and cardiometabolic risk factors adjusted for sex, school location, mother’s educational level, dietary misreporting, physical activity and BMI. There was a 0.124 mmol/L (95%CI: 0.002, 0.086) increase in the adolescent’s triglycerides level for every 1 unit SD increase in the identified DP z-score. Adolescents with higher adherence to the identified DP had three times higher odds of having dyslipidaemia (OR=2.68; 95%CI: 1.290, 5.565), elevated total cholesterol (OR=2.68; 95%CI: 1.290, 5.565) and abnormal LDL-C level (OR=3.01; 95%CI: 1.553, 5.189) compared to adolescents with lower adherence to this DP. Female and male adolescents in the third tertile of the DP had significantly three times higher odds of having elevated LDL-C (OR=2.48; 95%CI: 1.16, 5.31) and 28 times higher odds of having elevated serum insulin (OR=27.55; 95%CI: 1.171, 648.263) compared to their counterparts in the first tertile of the DP, respectively. There was no significant association reported between identified DP and obesity among this study adolescents. A DP high in free sugar but not fat was associated with increased risk of having dyslipidaemia, and abnormal levels of triglycerides, total cholesterol and LDL-C among study adolescents. Further longitudinal study are recommended to investigate the association between Malaysian adolescents’ diet and cardiometabolic risk factors, to prevent reverse causality. Identification of early dietary behaviours among adolescents might offer valuable information for prevention strategies of cardiometabolic risk development in later life.